Perlindungan Hukum dan Perspektif Kriminologi Terhadap Pelecehan Seksual di Fasilitas Publik - Anggarawan Tri Jayanto; Vieta Imelda Cornelis; Moh. Taufik (JOURNAL OF SHARIA ECONOMICS, 2022)
The crime of raping a child committed by a biological father is a formof sexual violence that is very concerning and has become a deepsocial and legal problem. This article aims to analyze the criminalliability of perpetrators of child rape by the biological father, byhighlighting various aspects of Indonesian criminal law, childprotection law, and the role of psychology in exploring the factors thatencourage this criminal act. The method used in this research is aqualitative approach with literature study and in-depth interviews withsources consisting of legal practitioners and forensic psychologyexperts. The results of the research show that perpetrators of childrape by the biological father can be charged with various articles inthe Criminal Code (KUHP), including articles on rape and sexualviolence against children, as well as factors that aggravate theconsequences of family relationships. This article also recommendsthe need for a multidisciplinary approach in handling this case,including preventive efforts involving the family, community and state.